A soft pack battery process protective film and preparation method thereof
By optimizing the adhesive layer components, a soft lithium battery protective film that is resistant to high temperature, chemical corrosion and moderate viscosity is prepared, which solves the shortcomings of the existing protective film in terms of high temperature, chemical corrosion and stability, and achieves better protection effect and application performance.
Patent Information
- Application Number
- CN202411982684.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
The existing soft-pack lithium battery protective film adhesive components have shortcomings in high temperature resistance, chemical corrosion resistance and stability, resulting in too small or too large viscosity, affecting the application effect of the protective film.
By optimizing the components of glue layer A and glue layer B, using isooctyl acrylate, glycidyl methacrylate, acrylic acid, hydroxyethyl acrylate and azobiisobutyl cyanide and other materials, combined with rosinol modified resin 6000A, epoxy resin and isopropanol, a protective film that is resistant to high temperature, chemical corrosion and moderate viscosity is prepared.
The prepared protective film has good high temperature resistance and chemical corrosion resistance, high stability, high hardness, good wear resistance, strong adhesion, difficult to fall off, and no colloid remains during the subsequent separation process.
Smart Images

Figure BDA0005221884950000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of protective films, and specifically relates to a soft-pack battery process protective film and a preparation method thereof. Background Art
[0002] Lithium-ion battery (Li-ion battery) is a type of rechargeable (secondary battery) battery that is widely used in consumer electronics, electric vehicles, energy storage systems, etc. due to its high energy density, long cycle life and low self-discharge rate.
[0003] Lithium-ion batteries achieve the charging and discharging process by the movement of lithium ions between the positive and negative electrodes: During charging: lithium ions are deintercalated from the positive electrode material, migrate to the negative electrode through the electrolyte, and are embedded in the negative electrode material; During discharging: lithium ions are deintercalated from the negative electrode material, migrate to the positive electrode through the electrolyte, and are embedded in the positive electrode material. The main components of lithium-ion batteries, the positive electrode material is usually composed of lithium compounds, such as lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese cobalt oxide or lithium iron phosphate; the choice of positive electrode material affects the energy density, power density, safety and cost of the battery. The negative electrode material is usually graphite, but silicon-based materials or other new materials may also be used. The negative electrode material determines the capacity and charging and discharging speed of the battery. The electrolyte is generally an organic solvent containing lithium salts; the electrolyte provides a medium for the migration of lithium ions between the positive and negative electrodes.
[0004] Lithium battery protective film is a film specially designed to protect lithium-ion batteries. It plays a vital role in the safety and performance of batteries. This protective film is usually applied to the outside of the battery to provide physical and chemical protection. There are two main types of lithium-ion battery shell processing: hard pack and soft pack. The hard pack lithium battery shell material is generally aluminum shell, steel shell and other metals, and the soft pack lithium battery shell material is generally aluminum plastic film.
[0005] Common lithium battery protective film materials include: Polyester: has good mechanical strength, chemical resistance and transparency, and is widely used in various types of battery protection; Polypropylene: is lightweight and flexible, has good impact resistance and heat resistance, and is suitable for occasions requiring higher temperature stability; Polyurethane: provides excellent wear resistance and elasticity, and is suitable for applications with high requirements for wear resistance; Aluminum-plastic composite film: combines the advantages of metal aluminum foil and plastic, provides excellent barrier properties and physical protection, and is often used in soft-pack batteries; Functional coatings: such as anti-stick coatings, fire-retardant coatings, thermal conductive coatings, etc., can be added to the protective film according to specific needs to enhance its performance.
[0006] Soft-pack protective films often contain glue components, but the existing glue is insufficient in terms of high temperature resistance, chemical corrosion resistance and stability. Some glues have too low viscosity, and the protective film will shift or fall off during the manufacturing process; some glues have too high viscosity, and when removed, colloid will remain or damage the battery surface, which is not conducive to the application of soft-pack protective films. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a protective film for a soft-pack battery process. By selecting and optimizing the components of the glue layer A and the glue layer B, the components are made to have the characteristics of high temperature resistance, chemical corrosion resistance, and moderate viscosity. The components are then composited and hot-pressed with a protective layer and a heat-sealing layer to obtain a soft-pack protective film with excellent performance.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A soft-pack battery process protective film comprises a protective layer, a glue layer A, a glue layer B and a heat-sealing layer which are arranged in sequence from the outside to the inside; the protective layer is a modified BOPP plastic film; the glue layer A comprises isooctyl acrylate, glycidyl methacrylate, acrylic acid, hydroxyethyl acrylate and azobisisobutyl cyanide; the glue layer B comprises rosin phenol modified resin 6000A, epoxy resin and isopropyl alcohol; the heat-sealing layer is a polypropylene or polyethylene layer.
[0010] Furthermore, the modified BOPP plastic film is a magnesium aluminum double hydroxide and glass fiber modified BOPP plastic film.
[0011] Furthermore, the adhesive layer A comprises, by weight, 20-30 parts of isooctyl acrylate, 1-2 parts of glycidyl methacrylate, 0.5-1 parts of acrylic acid, 8-12 parts of hydroxyethyl acrylate and 0.8-1.6 parts of azobisisobutyl cyanide.
[0012] Furthermore, the adhesive layer B includes 4-8 parts of rosin phenol modified resin 6000A, 10-20 parts of epoxy resin and 5-10 parts of isopropyl alcohol in parts by weight.
[0013] Furthermore, the thickness ratio of the protective layer, the adhesive layer A, the adhesive layer B and the heat-sealing layer is 0.5:0.7-1:1-1.2:0.8.
[0014] A method for preparing a protective film for a soft-pack battery process comprises the following steps:
[0015] S1: prepare magnesium aluminum double hydroxide and glass fiber respectively; take 30-40 parts of BOPP plastic film and put it into a stirring tank, increase the temperature to 155-165° C., add 0.5-1.5 parts of magnesium aluminum double hydroxide and 0.8-1.6 parts of glass fiber thereto, stir and react for 45-65 minutes, and obtain a modified BOPP plastic film;
[0016] S2: Mix 20-30 parts of isooctyl acrylate, 1-2 parts of glycidyl methacrylate, 0.5-1 parts of acrylic acid, 8-12 parts of hydroxyethyl acrylate and 0.8-1.6 parts of azobisisobutyl cyanide, raise the temperature to 80-90°C, and stir the mixture for 30-60 minutes under nitrogen protection to obtain a glue layer A;
[0017] S3: Mix 4-8 parts of rosin phenol modified phenolic resin, 10-20 parts of epoxy resin and 5-10 parts of isopropanol, stir and react at a temperature of 130-150°C for 40-55 minutes to obtain a glue layer B;
[0018] S4: stacking the protective layer, adhesive layer A, adhesive layer B and heat sealing layer in sequence from the inside to the outside, and after drying, the soft-pack battery process protective film can be obtained.
[0019] Furthermore, the preparation process of the magnesium aluminum double hydroxide in step S1 is: dissolving magnesium chloride and aluminum chloride in distilled water and stirring evenly, then dropping sodium hydroxide solution into the solution, stirring and mixing, and standing at a constant temperature of 60° C. for 24 hours, filtering, washing, and drying, and then placing the powder in a constant temperature box at 80° C. and heating for 5 hours, and grinding the obtained solid into powder to obtain layered magnesium aluminum double hydroxide powder.
[0020] Furthermore, step S2 further comprises 8-12 parts of maleic anhydride grafted ethylene octene copolymer.
[0021] Furthermore, the preparation process of the rosin phenol modified phenolic resin in step S3 is: take 10-20 parts of rosin phenol and add it into a reaction kettle, melt it at a temperature of 200-210°C, then add 15-25 parts of phenolic resin thereto, keep the temperature for reaction for 5-10 minutes, and then stir the reaction at a rate of 500r / min for 30-60 minutes.
[0022] Furthermore, in step S4, the drying temperature is 100-110° C., and the drying time is 1-2 hours.
[0023] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0024] The present invention uses isooctyl acrylate, glycidyl methacrylate, acrylic acid, hydroxyethyl acrylate and azobisisobutyl cyanide to obtain adhesive layer A; uses rosin phenol modified resin 6000A, epoxy resin and isopropyl alcohol to obtain adhesive layer B; uses magnesium aluminum double hydroxide and glass fiber modified BOPP plastic film as a protective layer; and then presses the protective layer, adhesive layer A, adhesive layer B and heat sealing layer to form a protective film. The prepared protective film is resistant to high temperature, chemical corrosion such as electrolyte, and has high stability; it has high hardness and good wear resistance, and can prevent the soft-pack lithium battery cell from being scratched during the production process; it has strong adhesion, is not easy to fall off, and is tightly combined with the surface without warping; in the subsequent separation, after applying solvents such as ethanol, it can be separated from the surface of the cell, and no colloid remains. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] A soft-pack battery process protective film of the present embodiment includes a protective layer, a glue layer A, a glue layer B and a heat-sealing layer arranged in sequence from the outside to the inside; the protective layer is a modified BOPP plastic film; the glue layer A includes isooctyl acrylate, glycidyl methacrylate, acrylic acid, hydroxyethyl acrylate and azobisisobutyl cyanide; the glue layer B includes rosin phenol modified resin 6000A, epoxy resin and isopropyl alcohol; the heat-sealing layer is a polypropylene or polyethylene layer.
[0027] The modified BOPP plastic film of this embodiment is a magnesium aluminum double hydroxide and glass fiber modified BOPP plastic film.
[0028] In this embodiment, the adhesive layer A includes 20-30 parts of isooctyl acrylate, 1-2 parts of glycidyl methacrylate, 0.5-1 parts of acrylic acid, 8-12 parts of hydroxyethyl acrylate and 0.8-1.6 parts of azobisisobutyl cyanide in parts by weight.
[0029] In this embodiment, the adhesive layer B includes 4-8 parts of rosin phenol modified resin 6000A, 10-20 parts of epoxy resin and 5-10 parts of isopropyl alcohol in parts by weight.
[0030] In this embodiment, the thickness ratio of the protective layer, adhesive layer A, adhesive layer B and heat-sealing layer is 0.5:0.7-1:1-1.2:0.8.
[0031] A method for preparing a soft-pack battery process protective film in this embodiment includes the following steps:
[0032] S1: prepare magnesium aluminum double hydroxide and glass fiber respectively; take 30-40 parts of BOPP plastic film and put it into a stirring tank, increase the temperature to 155-165° C., add 0.5-1.5 parts of magnesium aluminum double hydroxide and 0.8-1.6 parts of glass fiber thereto, stir and react for 45-65 minutes, and obtain a modified BOPP plastic film;
[0033] S2: Mix 20-30 parts of isooctyl acrylate, 1-2 parts of glycidyl methacrylate, 0.5-1 parts of acrylic acid, 8-12 parts of hydroxyethyl acrylate and 0.8-1.6 parts of azobisisobutyl cyanide, raise the temperature to 80-90°C, and stir the mixture for 30-60 minutes under nitrogen protection to obtain a glue layer A;
[0034] S3: Mix 4-8 parts of rosin phenol modified phenolic resin, 10-20 parts of epoxy resin and 5-10 parts of isopropanol, stir and react at a temperature of 130-150°C for 40-55 minutes to obtain a glue layer B;
[0035] S4: stacking the protective layer, adhesive layer A, adhesive layer B and heat sealing layer in sequence from the inside to the outside, and after drying, the soft-pack battery process protective film can be obtained.
[0036] The preparation process of the magnesium aluminum double hydroxide described in step S1 of this embodiment is: dissolving magnesium chloride and aluminum chloride in distilled water and stirring evenly, then dropping sodium hydroxide solution into the solution, stirring and mixing, and standing at a constant temperature of 60° C. for 24 hours, filtering, washing, and drying, and then placing the powder in a constant temperature box at 80° C. and heating for 5 hours, and grinding the obtained solid into powder to obtain layered magnesium aluminum double hydroxide powder.
[0037] Step S2 of this embodiment also includes 8-12 parts of maleic anhydride grafted ethylene octene copolymer.
[0038] The preparation process of the rosin phenol modified phenolic resin in step S3 of this embodiment is: take 10-20 parts of rosin phenol and add it into a reaction kettle, melt it at a temperature of 200-210°C, then add 15-25 parts of phenolic resin thereto, keep the temperature for reaction for 5-10 minutes, and then stir and react at a rate of 500r / min for 30-60 minutes.
[0039] In step S4 of this embodiment, the drying temperature is 100-110° C. and the drying time is 1-2 hours.
[0040] Example 1
[0041] This embodiment provides a method for preparing a soft-pack battery process protective film, comprising the following steps:
[0042] S1: 5g of magnesium chloride and 3g of aluminum chloride are dissolved in 50g of distilled water and stirred evenly, then 2g of sodium hydroxide solution is added dropwise to the solution, stirred and mixed, and then allowed to stand at a constant temperature of 60°C for 24h, filtered, washed, dried, and then the powder is placed in a constant temperature box at 80°C and heated for 5h, and the obtained solid is ground into powder to obtain layered magnesium aluminum double hydroxide powder;
[0043] 30g of BOPP plastic film was put into a stirring tank, the temperature was raised to 155°C, 0.5g of magnesium aluminum double hydroxide and 0.8g of glass fiber were added thereto, and the reaction was stirred for 45 minutes to obtain a modified BOPP plastic film layer;
[0044] S2: Mix 20 g of isooctyl acrylate, 1 g of glycidyl methacrylate, 8 g of maleic anhydride grafted ethylene octene copolymer, 0.5 g of acrylic acid, 8 g of hydroxyethyl acrylate and 0.8 g of azobisisobutyl cyanide, raise the temperature to 80°C, and react under nitrogen protection for 30 min with stirring to obtain a glue layer A;
[0045] S3: 10g of rosin phenol was added to a reactor and melted at 200°C, and then 15g of phenolic resin was added thereto, and the mixture was kept warm for 5 minutes, and then stirred at 500r / min for 30 minutes; 4g of rosin phenol-modified phenolic resin, 10g of epoxy resin and 5g of isopropanol were mixed, and the mixture was stirred at 130°C for 40 minutes to obtain a glue layer B;
[0046] S4: According to the thickness ratio of 0.5:0.7:1:0.8, the modified BOPP plastic film layer, the adhesive layer A, the adhesive layer B and the polypropylene heat sealing layer are stacked from the inside to the outside in sequence, and the drying temperature is 100° C. and the drying time is 1 hour to obtain the soft-pack battery process protective film.
[0047] Example 2
[0048] This embodiment provides a method for preparing a soft-pack battery process protective film, comprising the following steps:
[0049] S1: 10g of magnesium chloride and 8g of aluminum chloride are dissolved in 80g of distilled water and stirred evenly, then 5g of sodium hydroxide solution is added dropwise to the solution, stirred and mixed, and then allowed to stand at a constant temperature of 60°C for 24h, filtered, washed, dried, and then the powder is placed in a constant temperature box at 80°C and heated for 3h, and the obtained solid is ground into powder to obtain layered magnesium aluminum double hydroxide powder;
[0050] 40g of BOPP plastic film was put into a stirring kettle, the temperature was raised to 165°C, 1.5g of magnesium aluminum double hydroxide and 1.6g of glass fiber were added thereto, and the reaction was stirred for 65 minutes to obtain a modified BOPP plastic film layer;
[0051] S2: 30g of isooctyl acrylate, 2g of glycidyl methacrylate, 12g of maleic anhydride grafted ethylene octene copolymer, 1g of acrylic acid, 12g of hydroxyethyl acrylate and 1.6g of azobisisobutyl cyanide were mixed, the temperature was raised to 90°C, and the mixture was stirred and reacted for 60min under nitrogen protection to obtain a glue layer A;
[0052] S3: 20g of rosin phenol was added to a reactor and melted at 210°C, followed by adding 25g of phenolic resin, and reacting at this temperature for 10min, followed by stirring at a rate of 500r / min for 60min; 8g of rosin phenol-modified phenolic resin, 20g of epoxy resin and 10g of isopropanol were mixed, and reacted at 150°C for 55min with stirring to obtain a glue layer B;
[0053] S4: According to the thickness ratio of 0.5:1:1.2:0.8, the modified BOPP plastic film layer, the adhesive layer A, the adhesive layer B and the polypropylene heat sealing layer are stacked from the inside to the outside in sequence, and the drying temperature is 110° C. and the drying time is 2 hours to obtain the soft-pack battery process protective film.
[0054] Example 3
[0055] This embodiment provides a method for preparing a soft-pack battery process protective film, comprising the following steps:
[0056] S1: 7g of magnesium chloride and 6g of aluminum chloride are dissolved in 65g of distilled water and stirred evenly, then 3g of sodium hydroxide solution is added dropwise to the solution, stirred and mixed, and then allowed to stand at a constant temperature of 60°C for 24h, filtered, washed, dried, and then the powder is placed in a constant temperature box at 80°C and heated for 5h, and the obtained solid is ground into powder to obtain layered magnesium aluminum double hydroxide powder;
[0057] 35g of BOPP plastic film was put into a stirring kettle, the temperature was raised to 160°C, 1g of magnesium aluminum double hydroxide and 1.2g of glass fiber were added thereto, and the reaction was stirred for 60 minutes to obtain a modified BOPP plastic film layer;
[0058] S2: 25 g of isooctyl acrylate, 1.5 g of glycidyl methacrylate, 10 g of maleic anhydride grafted ethylene octene copolymer, 0.7 g of acrylic acid, 10 g of hydroxyethyl acrylate and 1.2 g of azobisisobutyl cyanide were mixed, the temperature was raised to 85°C, and the mixture was stirred and reacted for 45 min under nitrogen protection to obtain a glue layer A;
[0059] S3: 16g of rosin phenol was added to a reactor and melted at 205°C, followed by adding 22g of phenolic resin, and reacting at this temperature for 7min, followed by stirring at 500r / min for 50min; 6g of rosin phenol-modified phenolic resin, 15g of epoxy resin and 8g of isopropanol were mixed, and reacted at 145°C for 50min, to obtain a glue layer B;
[0060] S4: According to the thickness ratio of 0.5:0.8:1.1:0.8, the modified BOPP plastic film layer, the adhesive layer A, the adhesive layer B and the polypropylene heat sealing layer are stacked from the inside to the outside in sequence, and the drying temperature is 105°C and the drying time is 1.5 hours to obtain the soft-pack battery process protective film.
[0061] Comparative Example 1
[0062] The difference from Example 1 is that the layered magnesium aluminum double hydroxide powder is missing in step S1, and the other steps remain unchanged.
[0063] Comparative Example 2
[0064] The difference from Example 1 is that glass fiber is missing in step S1, and other steps remain unchanged.
[0065] Comparative Example 3
[0066] The difference from Example 1 is that the maleic anhydride grafted ethylene octene copolymer is missing in step S2, and the other steps remain unchanged.
[0067] Comparative Example 4
[0068] The difference from Example 1 is that the rosin phenol-modified phenolic resin is missing in step S3, and the other steps remain unchanged.
[0069] Performance testing:
[0070] The 180° peeling force was tested according to GB / T2792-2014 standard; 150°C, 30min baking high temperature peeling, 150°C, 30min high temperature shrinkage; insulation and other tests. The results are as follows:
[0071] Table 1
[0072]
[0073] From the above performance test results, it can be seen that the protective films prepared in Examples 1-3 have good high temperature resistance, corrosion resistance, insulation, peeling resistance and other properties. In particular, Example 3 has better comprehensive performance. However, because Comparative Examples 1-4 do not adopt the necessary technical solutions, their corresponding performance tests are significantly worse than those of the Examples. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0074] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A soft pack battery process protective film, characterized in that: It includes a protective layer, an adhesive layer A, an adhesive layer B and a heat-sealing layer which are arranged in sequence from the outside to the inside; the protective layer is a modified BOPP plastic film; the adhesive layer A includes isooctyl acrylate, glycidyl methacrylate, acrylic acid, hydroxyethyl acrylate and azobisisobutyl cyanide; the adhesive layer B includes rosin phenol modified resin 6000A, epoxy resin and isopropyl alcohol; the heat-sealing layer is a polypropylene or polyethylene layer.
2. A soft pack battery process protective film according to claim 1, characterized in that: The modified BOPP plastic film is a magnesium aluminum double hydroxide and glass fiber modified BOPP plastic film.
3. The soft pack battery process protective film according to claim 1, characterized in that: In parts by weight, the adhesive layer A comprises 20-30 parts of isooctyl acrylate, 1-2 parts of glycidyl methacrylate, 0.5-1 parts of acrylic acid, 8-12 parts of hydroxyethyl acrylate and 0.8-1.6 parts of azobisisobutyl cyanide.
4. The soft pack battery process protective film according to claim 1, characterized in that: In parts by weight, the adhesive layer B includes 4-8 parts of rosin phenol modified resin 6000A, 10-20 parts of epoxy resin and 5-10 parts of isopropyl alcohol.
5. The soft pack battery process protective film according to claim 1, characterized in that: The thickness ratio of the protective layer, the adhesive layer A, the adhesive layer B and the heat-sealing layer is 0.5:0.7-1:1-1.2:0.
8.
6. A method for preparing a protective film for a soft-pack battery process, characterized in that: The steps include: S1: prepare magnesium aluminum double hydroxide and glass fiber respectively; take 30-40 parts of BOPP plastic film and put it into a stirring tank, increase the temperature to 155-165° C., add 0.5-1.5 parts of magnesium aluminum double hydroxide and 0.8-1.6 parts of glass fiber thereto, stir and react for 45-65 minutes, and obtain a modified BOPP plastic film; S2: Mix 20-30 parts of isooctyl acrylate, 1-2 parts of glycidyl methacrylate, 0.5-1 parts of acrylic acid, 8-12 parts of hydroxyethyl acrylate and 0.8-1.6 parts of azobisisobutyl cyanide, raise the temperature to 80-90°C, and stir the mixture for 30-60 minutes under nitrogen protection to obtain a glue layer A; S3: Mix 4-8 parts of rosin phenol modified phenolic resin, 10-20 parts of epoxy resin and 5-10 parts of isopropanol, stir and react at a temperature of 130-150°C for 40-55 minutes to obtain a glue layer B; S4: stacking the protective layer, adhesive layer A, adhesive layer B and heat sealing layer in sequence from the inside to the outside, and after drying, the soft-pack battery process protective film can be obtained.
7. The method for preparing a soft pack battery process protective film according to claim 6, characterized in that: The preparation process of the magnesium aluminum double hydroxide described in step S1 is: dissolving magnesium chloride and aluminum chloride in distilled water and stirring evenly, then dropping sodium hydroxide solution into the solution, stirring and mixing, and standing at a constant temperature of 60° C. for 24 hours, filtering, washing, and drying, and then placing the powder in a constant temperature box at 80° C. and heating for 5 hours, and grinding the obtained solid into powder to obtain layered magnesium aluminum double hydroxide powder.
8. The method for preparing a soft-pack battery process protective film according to claim 6, characterized in that: Step S2 also includes 8-12 parts of maleic anhydride grafted ethylene octene copolymer.
9. The method for preparing a soft-pack battery process protective film according to claim 6, characterized in that: The preparation process of the rosin phenol modified phenolic resin in step S3 is as follows: 10-20 parts of rosin phenol are added to a reaction kettle, melted at a temperature of 200-210° C., then 15-25 parts of phenolic resin are added thereto, kept warm for 5-10 minutes, and then stirred at a rate of 500 r / min for 30-60 minutes.
10. The method for preparing a soft pack battery process protective film according to claim 6, characterized in that: In step S4, the drying temperature is 100-110° C., and the drying time is 1-2 hours.